Analisis Penerapan Sistem Informasi Manajemen Kepegawaian Di Kantor Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia Kota Padangsidimpuan - Wawan Patriansyah; Tri Eva Juniasih; Rina Tiur Lona; Ade Maya Mei shanty Lubis (Concept: Journal of Social Humanities and Education, 2023)
In this era of digital revolution, technological developments have occurred in an evolution in media technology and one of them is the personnel management information system. The management information system assists in carrying out the duties of all State Civil Apparatuses within the Civil Service Agency and Human Resources Development in the city of Padangsidimpuan. Judging from the importance of SIMPEG, this research will analyze how SIMPEG is implemented in the Office of the Personnel and Human Resources Development Agency in Padangsidimpuan City. The aim is to find out the SIMPEG implementation process and the obstacles experienced, as well as how it impacts the community related to the Personnel and Human Resources Development Agency of the City of Padangsidimpuan. The research method used was by distributing questionnaires filled in by employees. The results of this study are that the application of SIMPEG in the Office of the Personnel and Human Resources Development Agency in the city of Padangsidimpuan is in the effective category which makes it easier for employees to carry out their work and speeds up administrative processes, especially in the field of staffing.